ANALYZING THE SPECIFICS AND SUMMARIZING THE EXPERIENCE OF IMPLEMENTING INNOVATIVE EDUCATIONAL TECHNOLOGIES IN THE TEACHING OF TH COURSE "TECHNOLOGICAL SCHEMES AND BASIC EQUIPMENT OF PUMPING STATIONS". - Prokopenko, O.; Antonenko, N. (Problems of Engineer-Pedagogical Education, 2023)
In this paper, we put forward essential resources that provide valuable insights into the pressing matters concerning the preparation of vocational education graduates for the oil and gas industry. These resources encompass various scientific and pedagogical aspects, thereby offering comprehensive expertise in the field. The article covers the interconnection between providing education opportunities to people who are at a considerable distance from an education institution or do not have the opportunity to attend face-to-face classes and the development of distance learning models on which the educational environment of a higher education institution is based. The analysis focuses on the educational course "Technological Schemes and Basic Equipment of Pumping Stations," tailored for first-level (bachelor's degree) higher education students in the field of Vocational Education (specifically, the extraction, processing, and transportation of minerals) within the educational program "Vocational Education (Oil and Gas)." This course model was devised at the Department of Automation, Metrology and Energy-Efficient Technologies at Ukrainian Engineering Pedagogics Academy. The study delves into scientific and pedagogical outcomes resulting from the integration of innovative technologies within the educational curriculum. The utilization of this model effectively enables the provision of accessible and high-quality education within a university setting, especially during military operations or situations where limited physical attendance is possible for participants engaged in the academic process. The relevance of creating and implementing the model in the educational process is substantiated. The results of its implementation based on the Moodle system are presented. The structure and features of the model and the factors affecting them are analyzed. The principles of didactics and a group of principles considering the specifics of distance learning, on which the model is based, are determined. The scientific approaches, based on which the model was developed and implemented, are characterized. The use of innovative technologies in the development of individual elements for the model is shown. The factors that were considered during the implementation of the personal components of the discipline content are identified and classified. The study substantiates that the success of implementing innovative educational technologies relies on establishing a straightforward feedback mechanism via a robust communication toolset within the Moodle system. It also highlights the effectiveness achieved by combining diverse interaction methods through modern information technologies, thereby facilitating a comprehensive evaluation of students' progress and accomplishments throughout the educational process.